SKEMA PEMBIAYAAN DALAM PERBANKAN SYARIAH - Riska Febrian; Aprilia Rahmasari; Kharisma Tri Buana Dewi; Renny Oktafia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Sharia banking is a body that oversees public finances in the form of savings and returns to the community in the form of financing. Banking is a solution to problems to achieve community economic prosperity. The aim of this research is to explain the basic concepts of financing in sharia banking using library research. The final results obtained show that financing carried out by banks is carried out using financing feasibility analysis for customers before providing financing using a funding analysis approach, application of funding analysis principles, application of funding analysis procedures and policies in funding decisions.